Hand Wrist Bone Identification Using Quadrant Ballon Snake - Riyanto Sigit; Moch. Rochmad; Tri Harsono; Farah Devi Isnanda (Institute of Advanced Engineering and Science, 2017)
In this research, hand wrist bone Identification for human forensic is discussed. Hand wrist bone is one of the effective methods used in the forensic science for age identification. There are four techniques used in this research: cropping image, preprocessing, Quadrant Ballon Snake and identification. The first step is to crop an image on metaphysis and epiphysis bone. The second step is preprocessing using morphology and edge detection. The third step is to apply Quadrant Ballon Snake to segment hand wrist bone. The last step is to use ratio metaphysis and epiphysis to identify a person. The performance segmentation for assessment hand wrist bone showed an average age identification 91%, bone age metaphysis 95% and bone age epiphysis 95%. The experiments resulted in the fact that Quadrant Ballon Snake method is able to find and improve the segmentation of hand wrist bone images accurately. This indicates that this method is effective for segmenting hand wrist bone.